Study on the design, synthesis, and activity of anti-tumor staple peptides targeting MDM2/MDMX - Yang, Jian; Liao, Xiufei; Hu, Damin; Mo, Jinqiu; Gao, Xiurong; Liao, Hongli (Frontiers in Chemistry, 2024)
Staple peptides, which have a significantly enhanced pharmacological profile, are promising therapeutic molecules due to their remarkable resistance to proteolysis and cell-penetrating properties. In this study, we designed and synthesized a series of PMI-M3-based dual-targeting MDM2/MDMX staple peptides, and compared with the straight-chain peptides, the stapler peptide SM3-4 screened in the study induced apoptosis of tumor cells in vitro at low μM concentrations, and the helix was significantly increased. Studies have shown that the enhancement of staple activity is related to the increase of helicity, and SM3-4 provides an effective research basis for dual-targeted anti-tumor staple peptides.